Modern Approaches to the Management of Children with Acute Respiratory Viral Infection - Baranov, Aleksander A.; Namazova-Baranova, Leyla S.; Lobzin, Yuri V.; Tatochenko, Vladimir K.; Uskov, Aleksandr N.; Kulichenko, Tatiana V.; Vishneva, Elena A.; Kolbin, Alexey S.; Novik, Gennady A.; Bulgakova, Vilya A.; Bakradze, Maiya D.; Polyakova, Anastasiya S.; et al. (Pediatricheskai͡a︡ farmakologii͡a︡ : nauchno-prakticheskiĭ zhurnal Soi͡u︡za pediatrov Rossii, 2023)
Experts of the Union of Pediatricians of Russia have developed modern guidelines on management of children with acute respiratory viral infection. The term “acute respiratory viral infection” (ARVI) combines following nosological forms: acute nasopharyngitis, acute pharyngitis, acute laryngitis, acute tracheitis, acute laryngopharyngitis, upper respiration tract infection (unspecified). The issues of epidemiology, diagnosis, treatment, and prevention have been considered in detail.